Root reinforcement to soils provided by common Ethiopian highland plants for gully erosion control. Issue 6 (2nd February 2018) - Zegeye, Assefa D.; Langendoen, Eddy J.; Tilahun, Seifu A.; Mekuria, Wolde; Poesen, Jean; Steenhuis, Tammo S.
Abstract: Grasses and trees are often used to stabilize gully banks. However, the effectiveness of such biological conservation measures has not been investigated for the Ethiopian highlands. This study investigates the reinforcement that plant roots may provide to strengthen gully banks in Ethiopia. The root systems of 26 indigenous and exotic plant species of 3 plant life forms (grasses, shrubs, and trees) were sampled, and root tensile strength and distribution were determined. The RipRoot model was used to quantify the additional cohesion derived from the plant roots. Among all tested roots, Eleusine floccifolia (grass), Tephrosia vogelii (tree), and Rosa abyssinica (shrub) had the strongest roots for each life form. The root volumetric ratio (root volume divided by soil volume) in the top 0.6 m of soil ranged from 0.03% to 0.46% . Roots of Digitaria abyssinica provided the maximum added cohesion (10.6 kPa) over this depth. For a given plant species, root volumetric ratio had a greater effect on additional cohesion than root tensile strength. Plant species with a fibrous root system provided greater additional cohesion values in the top 0.6 m (on average 3.4 vs. 1.7 kPa for tap root systems) and could potentially enhance gully bank stability for shallow gullies more than plants having a tap root system. To effectively rehabilitate larger gullies, plants should be integrated with other gully rehabilitation measures, such as regrading of gully banks and structural measures such as check dams to trap sediments, thereby reducing the effective gully bank height relative to rooting depth.